2014
DOI: 10.1254/jphs.13274fp
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Inhibits Bortezomib-Induced Mechanical Allodynia Through Supraspinal Action in Mice

Abstract: Bortezomib, an inhibitor of proteasome holoenzyme, is used to treat relapsed and refractory multiple myeloma. Peripheral neuropathy is a treatment-limiting adverse effect of bortezomib and is very difficult to control. In this study, we examined the efficacy of gabapentin in inhibiting bortezomib-induced peripheral neuropathy. Single intravenous injections of bortezomib (0.03 - 0.3 mg/kg) dose-dependently induced mechanical allodynia with a peak effect 12 days after injection. Bortezomib (0.3 mg/kg) also cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
(40 reference statements)
3
18
0
Order By: Relevance
“…However, in vitro concentrations of Phα1β required to block TRPA1 channels are similar to those required to block VGCC (Vieira et al, ), suggesting that, in vivo, the actions of Phα1β could depend on VGCC inhibition. In agreement with a previous report (Kitamura et al, ), we failed to observe any protective effect by either i.pl. or i.t.…”
Section: Discussionsupporting
confidence: 94%
“…However, in vitro concentrations of Phα1β required to block TRPA1 channels are similar to those required to block VGCC (Vieira et al, ), suggesting that, in vivo, the actions of Phα1β could depend on VGCC inhibition. In agreement with a previous report (Kitamura et al, ), we failed to observe any protective effect by either i.pl. or i.t.…”
Section: Discussionsupporting
confidence: 94%
“…Tanabe et al first reported the role of descending noradrenergic inhibition in gabapentin analgesia by demonstrating that depletion or blockade of noradrenergic signaling in the spinal cords of mice, after peripheral nerve injury, abolishes the antihypersensitivity effect of systemically administered gabapentin [25]. Similar behavioral results are also reported in various neuropathic pain rodent models, after systemic, intra-cerebroventricular, or intra-LC administration of gabapentin [26,27,28]. Gabapentin likely acts similarly in humans, because its oral administration at a dose that produces postoperative analgesia increases the noradrenaline concentration in the cerebrospinal fluid of patients with joint pain scheduled for orthopedic surgery [19].…”
Section: Gabapentinoidsmentioning
confidence: 88%
“…Gabapentin, originally licensed as an antiepileptic drug in 1993, was rapidly recognized as an analgesic in patients and animals with neuropathic pain [25,26,27,28]. Gabapentin interacts with the α2δ subunit of voltage-gated calcium channels that modulates the release of excitatory amino acids in the spinal dorsal horn [29] and produces analgesia in transgenic mice with up-regulated α2δ-1 subunits, but not in normal mice [30], suggesting that the efficacy of gabapentin relies on the α2δ subunit.…”
Section: Gabapentinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered levels of several neurotransmitters, such as catecholamines, histamine, serotonin, glutamate and γ-aminobutyric acid (GABA), are associated with CIPN caused by vincristine [152,153], paclitaxel [154], oxaliplatin [155][156][157] and bortezomib [158].…”
Section: Central Nervous System Structures and Neurotransmittersmentioning
confidence: 99%